Conversion of waste palm kernel cake into value-added materials using subcritical water reaction - Raja Zazalli, Raja Munawarrah (2019)
Waste palm kernel cake (PKC) is one of the oil palm biomasses with high potential for value-added materials. Waste PKC was characterized and the effect of reaction temperature of subcritical water treatment on the production of value-added materials was assessed. Next, the effect of reaction time on the production of value-added materials, especially sugar was investigated.